Analysis of Spare Part Sales Strategy at PT Traktor Nusantara Medan Branch - Adjie Ahmad Nugraha; Marliyah Marliyah (Penerbit Jurnal Indonesia, 2022)
This study aims to find out how the sales strategy of heavy equipment spare parts is. The location of this research was carried out at PT Traktor Nusantara Medan Branch which is located on Medan-Pematang Siantar road no.km.11, Amplas kec. Percut Sei Tuan, Deli Serdang district, North Sumatra 2014.9. The data collection methods used are the library method and the field method. The data sources in this study basically use two types of data, namely; primary data and secondary data. The results showed that the sales strategy of PT Traktor Nusantara Medan branch was quite good, but it would be better if given a little innovation to attract new buyers.